Planificación y Evaluación para los Aprendizajes en Educación Infantil desde un Enfoque de Derechos - Manhey, Mónica (Ariadna Ediciones, 2021)
This book by Dr. Manhey is a particular contribution to the bibliography in the areas of teaching work in the Early Childhood Education sector from a Rights Approach. From this powerful and respectful view of children and children focused on their rights, it can be planned by defining certain valuable intentions, without forcing their learning to a restricted vision of them and exclusively adult-centered as usual. The same happens with evaluation, which, if fully understood in terms of its purposes and essential characteristics and implemented with an appropriate approach, can provide valuable information on the learning that is being generated, which is what is offered. in the pages of this interesting book.